Bone remodeling is regulated by inner ear vestibular signals. (18th September 2013) - Vignaux, Guillaume; Besnard, Stéphane; Ndong, Jean; Philoxène, Bruno; Denise, Pierre; Elefteriou, Florent
ABSTRACT Bone remodeling allows the conservation of normal bone mass despite constant changes in internal and external environments. The adaptation of the skeleton to these various stimuli leads credence to the notion that bone remodeling is a true homeostatic function, and as such is under the control of specific centers in the central nervous system (CNS). Hypothalamic and brainstem centers, as well as the sympathetic nervous system (SNS), have been identified as regulators of bone remodeling. However, the nature of the afferent CNS stimuli that may modulate CNS centers involved in the control of bone remodeling, with the exception of leptin, remains unclear. Based on the partial efficacy of exercise and mechanical stimulation regimens to prevent microgravity‐induced bone loss and the known alterations in vestibular functions associated with space flights, we hypothesized that inner ear vestibular signals may contribute to the regulation of bone remodeling. Using an established model of bilateral vestibular lesions and microtomographic and histomorphometric bone analyses, we show here that induction of bilateral vestibular lesion in rats generates significant bone loss, which is restricted to weight‐bearing bones and associated with a significant reduction in bone formation, as observed in rats under microgravity conditions. Importantly, this bone loss was not associated with reduced locomotor activity or metabolic abnormalities, was accompanied with molecular signs of increased sympathetic outflow, and could be prevented by the β‐blocker propranolol. Collectively, these data suggest that the homeostatic process of bone remodeling has a vestibulosympathetic regulatory component and that vestibular system pathologies might be accompanied by bone fragility. © 2013 American Society for Bone and Mineral Research.